SQUAMOUS CELL CARCINOMA (SCC) TIROID: LAPORAN KASUS - Aulia Jasmine Mukti; M. Yamsun (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Squamous cell carcinoma of the thyroid gland is a rare thyroid tumor accounting for less than 1% of all cases of primary thyroid carcinoma. Squamous cell carcinoma of the thyroid gland is very aggressive and has a poor prognosis. There is no standard management outline that can be used as a guideline for treatment, which is a challenge for the treating team. This case report aims to further examine the pathological features, diagnosis, and treatment of thyroid SCC. We present a 73 years old male with progressive neck swelling, hoarse voice, accompanied by difficulty swallowing for 6 months prior to admission to the hospital who was referred to the oncologist as a suspected case of carcinoma of the thyroid. Computed tomography of the neck showed a 2,1 x 2,3 x 7,7 cm solid mass in the lateral dextra of the larynx and lymphadenopathy. Thorax Rontgen ruled out the possibility of metastasis. Thyroidectomy and debulking were performed on the patient. Anatomy pathological examination revealed squamous cell carcinoma.